2001
DOI: 10.1046/j.1523-1755.2001.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule selectin ligand inhibition improves outcome in ischemic acute renal failure

Abstract: Small molecule selectin ligand inhibition provides a novel and effective approach to attenuate ischemic acute renal failure. Timing of treatment is crucial to success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 32 publications
2
43
0
1
Order By: Relevance
“…Although ablation of the ICAM-1 gene and pretreatment with ICAM-1 antibody rendered mice resistant to ischemic AKI, human trials with anti-ICAM-1 mAb administered after ischemia did not prevent AKI in cadaveric transplant recipients (14). Similarly, gene knockouts, mAb, and pharmacologic inhibitor studies have suggested a role for E-and P-selectins (132)(133)(134). However, subsequent studies have shown that it is platelet P-selectin, not endothelial P-selectin, that is the key component leading to AKI (135).…”
Section: Alterations In the Microvasculaturementioning
confidence: 99%
“…Although ablation of the ICAM-1 gene and pretreatment with ICAM-1 antibody rendered mice resistant to ischemic AKI, human trials with anti-ICAM-1 mAb administered after ischemia did not prevent AKI in cadaveric transplant recipients (14). Similarly, gene knockouts, mAb, and pharmacologic inhibitor studies have suggested a role for E-and P-selectins (132)(133)(134). However, subsequent studies have shown that it is platelet P-selectin, not endothelial P-selectin, that is the key component leading to AKI (135).…”
Section: Alterations In the Microvasculaturementioning
confidence: 99%
“…Blockade of the shared ligand to all three selectins (E-, P-, and L-selectin), which appears to be dependent on the presence of a key fucosyl sugar on the selectin ligand, led to reduced injury and mortality. Further, mice genetically deficient for E-selectin or P-selectin or both were completely protected in the cecal ligation and puncture model (CLP), a preclinical model for sepsis (88,89).…”
Section: Endotheliummentioning
confidence: 99%
“…Although the inactive control was ineffective, a 50% inhibitory effect (IC 50 ) was achieved by BIMO at 500 M for E-selectin, 70 M for P-selectin, and 560 M for L-selectin. An in situ perfusion with BIMO before the I/R injury inflicted by bilateral artery clamping prevented mortality and improved kidney function (20). The damage caused by hemorrhagic shock was diminished after pretreatment with BIMO (21).…”
mentioning
confidence: 93%